Menjalani Kehidupan di Tengah Malapetaka: Gempa Kerinci 1909 - Hudaya, Padhil; Setiawati, Nur Aini; Purwanto, Bambang (Jurnal Sejarah Citra Lekha, 2023)
This paper discusses the ability of the Kerinci people to adapt during the recovery process after the earthquake catastrophic in June 1909, when they had to deal with massive damage, environmental changes, various internal limitations, inadequate support from external elements, and the impact of colonial political and military annexation. The research utilizes colonial government report documents, written records of eyewitnesses, newspaper reports, and oral traditions. Inspired by the concept of "everyday forms of resistance" from James C. Scott, the daily life of Kerinci people is understood as a resistance which is able to break free from dependency by utilizing its own socio-cultural potential. The Kerinci people fought against the disruption of the earthquake and were able to transform helplessness into strength. They did not depend on the colonial government in the process of rebuilding and recovering after the earthquake, because adat which has synergized with religion and love for the homeland, is able to make the population survive.